How does budget participation affect managerial performance in the higher education sector? a mediated-moderated model - Alhasnawi, Mushtaq Yousif; Mohd Said, Ridzwana; Alshdaifat, Sajead Mowafaq; Elorabi, Khaled Ahmed; Al-Hasnawi, Maytham Hameed; Khudhair, Ali Hussein (Emerald Publishing, 2024)
Purpose: Employee participation in budgeting enhances motivation and commitment, leading to better performance by enhancing ownership. Within Iraqi higher education institutions (HEIs), the current investigation delves into the influence of participative budgeting on managerial performance. Drawing upon goal-setting theory, this study discerns budget goal commitment as a mediating variable while also examining directive leadership as a moderator in the dynamics of this association. Design/methodology/approach: The current study used partial least squares structural equation modelling (PLS-SEM) using SmartPLS 4.0. 373 questionnaires were collected from managers in Iraqi public universities, with 58.37% responding. Findings: The findings show that budget goal commitment partially mediates the connection between budget participation and managerial performance. Furthermore, the results showed that directive leadership increases the positive associations between budget goal commitment and managerial performance. Originality/value: This study expands the existing literature by shedding light on the mediating role of budget goal commitment and the moderating influence of directive leadership. It also enriches the discourse in management accounting by providing a more elucidation of how employee involvement in the budgeting process enhances managerial performance.